USING CONFIRMATORY FACTOR ANALYSIS TO DETERMINE ROLES OF THE BOARD: EVIDENCE FROM MALAWI. - Mkandawire, K; Tcheleni, Betchani; Hussein, Mustafa (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2024)
The main purpose of this study is to analyse the key Board roles that improve the performance of directors in Malawi. The research investigates tasks that the board must execute to enhance its performance, ultimately contribute to the achievement of entity’s strategic goals. The study adopted the cross sectional survey design. A questionnaire was used to collect data from 174 board members who were drawn from board of directors from stock exchange listed companies, state owned enterprises, private companies and non governmental organisations. Data was analysed using IBM SPSS version 20. Descriptive and Confirmatory Factor Analyses were used to determine the key roles of the board. Findings suggest that the control, strategic and service are the key board roles in Malawi. The results further show that the control role is more significant than the other two roles. Using perceptions of the board, this study renders initial verifiable evidence of the significant roles of the board in Malawi. As such, the outcome of this study will be of interest to many corporate governance stakeholders including shareholders, board members, academia and regulatory bodies..